PENGARUH PROFESIONALISME, ETIKA PROFESI, PENGALAMAN, PENGETAHUAN MENDETEKSI KEKELIRUAN, MOTIVASI DAN KUALITAS AUDIT TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Empiris Pada Auditor KAP Di Kota Semarang) - Yulia Fransisca Rering, 14.05.52.0221; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
The purpose of this research is to analyse the influence of professionalism, professional ethcis , experiences ,auditorâs knowledge for errors, motivation and audit quality to the materiality level of judgement auditor who works in public accounting firm in Semarang. The population of this research are all auditor which have minimal 2 years job experience as auditor. Sampling was conducted using a purposive sampling method and number of samples of 61 respondents. The data were obtained from the primary source,collected by using survey method by distributing questionnaire directly. The data analysis technique used in this research is the technique of multiple regression analysis. The result showed that the professionalism, professional ethis, experiences, auditorâs knowledge for errors, motivation and audit quality have a positive and significant impact on the materiality level of judgement. Â Keywords:Â Professionalism, Professional Ethis, Experiences, Auditorâs Knowledge For Errors, Motivation, and Audit Quality Accountants Judgement of Materiality Level